Impact of Using Pendowo Liquid Organic Fertilizer Toward Land Potential at Jenar, Sragen, Central Java - Kaeksi, Retno Woro (Universitas Muhammadiyah Surakarta, 2002)
The objectives of this research are to know the content of chemical elements found in waste of fluid organic in Jenar Banker in sub district of Jenar, Sragen and to know the influence of fluid organic fertilizer on the potency of area in Jenar. The collected data in this research are 1) topography, 2) geology, 3) geomorphology process, 4) area used, 5) horizon of the soil, 6) soil texture, 7) soil structure, 8) pH of the soil, 9) Nitrogen, 10) Phosphate, 11) Calium, 12) Calcium, 13) Magnesium, 14) the characteristic of physics and chemical elements in waste of Pendowo fluid organic fertilizer, and 15) the data dealing with interviewing to the civilization. For getting the area taken as the sample, this research uses stratified random sampling. While the analysis used in this study is descriptive method. The result of this research shows that 1) the main stone as the material for forming the land consists of sandstone, tuff of sand, limestone and clay (eaten for medicinal puposes); the relief is wave until making the hill, the plant consists of jati (teak), sonokeling, and the seasonal plants that exist in tegalan (dry field near the rie field but used for vegetables and other secondary crops), farm, and tebu (sugar cane) land. The land that has not influenced by the amine fertilizer, the characteristi of pH soil is base (more than 7,5). The structure of crumbs up to clump soil and texture of clay which have sand are relevant with jati (teak) and sonokeling growth. 2) the chemical elements of fluid organi fertilizer in Banker are not relevant with the chemical elements which are proposed by Paluraya Company. The element of nitrogen proposed is 4% while the result of the research shows 3,93%; 3,6%; 2,26%; 0,887%; 0,09%; 0,137%; 0,171%; 0,156%; 0,187%; 0,167%; 0,175%; and 0,108%. The pH of the fertilizer proposed is 5,5 â 6,5 while the finding of the research shows there are pH 4,65; pH 3,6; pH 4,5; and pH 5,41. The element of phosphate proposed is 0,3% while the result of the research shows that is less of 0,3%, they are 0,22%; 0,1%; 0,001%; 0,0053%; 0,0095%; 0,0077%; 0,0053%; 0,0047%; 0,0052%; 0,0055%; and 0,0072%. The element of calcium proposed is 1,2% but the finding of the analysis from 9 sample of calcium elements are less of 0,2%. 3) The potency of the land lower from time to time and it will become serious problems because there is a series changes of soil structure to be clay strong, the forming of complex cropping board of salt, pedal lay and pH soil become sour. By becoming sour, so the growth of the pants and the development of the plants in the area of the research will be destroyed more over, they will not grow anymore.